Analisi Kesalahan Gramatika dalam Prosedur Text Bahasa Inggris pada Mahasiswa Kesehatan Masyarakat Universitas Faletehan - Soraya, Kety (JEDLISH : Journal Of Education and English Language Teaching, 2021)
The Second language of grammatical system may cause the problem in learning the target language in speaking, reading, listening, and writing. This study is intended to analyze, find out the types of errors, and the factors for grammatical error in students composition. The use of articles, verbs, adjectives, adverbs, nouns, preposition, and conjunctions are the focus of the analysis. The errors are analyzed through the procedure of identification, description, categorization, classification, calculation and interpretation. The errors were then classified into four types namely omission, addition, misformation, and misordering then they were counted and interpreted. Altogether they were 1143 errors in student’s procedure text. They covered 462 (40.41%) errors of articles, 230 (20.12%) errors of nouns, 195 (17.06%) errors of preposition, 76 (6.64%) errors of adjectives, 62 (5.42%) errors of verb, 58 (5.07%) errors of conjunction, 44 (3.84%) errors of pronouns, and 62 (5.42%) errors of verbs. Based on the type of errors omission errors got the highest frequency. It happened 431 (37.7%) followed by misformation and misordering, addition errors 138 (12.07%). There were various frequencies of errors found from each type. Omission errors included 190 (41.12%) from 462 errors of articles, Nouns 80 (34.78%) from 230 error of nouns, preposition 65 (33.33%) from 195 errors of prepositions, conjunction 30 (51.72%) from 58 errors of conjunction, pronoun 25 (52.83%) fro 44 of pronouns, verb 20 (32.25%) from 62 errors of verbs, adjective 20 (26.31%) from 76 errors of adjectives. Addition errors 65 ( 33.33 %) from 195 errors of preposition, nouns 25 (10.86 %) from 230 errors of nouns and adjective 20 (26.31 %) from 76 adjectives. The misordering errors of articles are clearly seen that they got the highest frequency among others. It books place 190 times (41.12%) from 462 of articles. Great tendency to omit and misform, article, nouns, and preposition is influenced by the skill habit of L1, as well as misordering errors of articles, preposition, nouns, and adjective. It is interpreted hat differences of the structure of L1 and L2 greattly influence the learners to make grammatical errors in writing English composition. Another factor tha the causes the errors in incomplete of the target language it self.